The Impact of Green Architecture on Energy Consumption in Highrise Office Buildings in Nairobi - Okemwa, Moses, N (University of Nairobi, 2017)
Based on the available scientific evidence, it is now more certain than ever that people are altering the climate. The temperatures in the atmosphere and even the in the oceans are rising, sea-levels are going up and the Arctic sea ice is waning. One of the major contributors of these climatic changes is the increased energy consumption due to rapid urbanization and growth in the building and construction industry both internationally and locally. The building and construction industry is one of the largest consumers of energy and also one the largest emitters of greenhouse gases in the world today. Urgent measures are therefore required to reduce energy consumption, control emissions during manufacturing, transportation and installation of building materials. The main objectives of this research was to establish if there are green buildings in the area of study, determine the impact of building services on energy consumption and subsequently establish the variations in energy consumption by building architecture. The study covered 42 buildings which formed 20% of all the tall office buildings within the study area. The research established that there exists green buildings within the study area with the best performing building being the Coca Cola headquarters in Upperhill attaining a 5 star rating based on the Green Star rating criteria; this building offers the best case study of how buildings within the tropics can be designed, constructed and operated to meet the requirements of a green building. This research recommends for formulation of a policy framework that will ensure that developers and existing office building owners incorporate renewable energy sources in their brief to supplement the energy from the national grid; the research further recommends for the formation of a national body that will ensure that new buildings are designed to meet the green building requirements that will subsequently lead to efficient use of energy within the building and construction industry